Supercritical CO2 Extraction of Natural Compounds from Capuchin (Tropaeolum majus) Leaves and Seeds - Corrêa, Gabriel [UNESP]; Souza, Michel Rubens dos Reis; Nascimento, Eduardo Soares [UNESP]; Rodrigues Bjerk, Thiago; Goncalves, José Eduardo; Moritz, Cristiane Mengue Feniman; Sakai, Otávio Akira; Silva, Erivaldo Antônio da [UNESP]; Santos, Renivaldo José dos [UNESP]; da Silva, Edson Antônio; Cardozo-Filho, Lucio; Zanette, Andreia Fatima [UNESP]; et al. (MDPI, 2024)
This study investigated the supercritical CO2 extraction of oils from capuchin (Tropaeolum majus) seeds (4.34% moisture content) and leaves (5.26% moisture content) and analyzed the effects of varying temperature and pressure conditions. The extraction yields were 3% for the seeds and 2% for the leaves. The seed extracts were rich in oleic, linoleic, and palmitic fatty acids, whereas the leaf extracts contained a high concentration of octacosanol (73.37%). Kinetic analysis revealed distinct mass transfer mechanisms during extraction, and the Sovová model effectively described the extraction kinetics, showing good agreement with experimental data (ADD% < 4%). An analysis of variance (ANOVA) demonstrated the impact of temperature and pressure on the yields, with temperature being the most influential factor. The experimental conditions ranged from 22 to 28 MPa and from 313.15 to 333.15 K. This study contributes to the understanding of capuchin oil extraction and its potential applications in various fields, owing to the presence of bioactive compounds.
Keywords: capuchin; CO2; octacosanol; oleic acid; supercritical extraction